علاقة البيئة الصفّية المحفِّزة بالتفكير الإبداعي لدى تلاميذ الصفوف العليا (الرابع، الخامس، والسادس): دراسة ميدانية في مدرستي الخنساء وطارق بن زياد - مدينة صرمان (Comprehensive Journal of Science, 2025)
This study aimed to investigate the nature of the relationship between the availability of a stimulating classroom environment (psychologically, physically, and organizationally) and the level of creative thinking (fluency, flexibility, originality) among upper elementary students. It also sought to examine differences in creativity attributable to gender and grade level variables.The study adopted a descriptive-analytical approach. Two main instruments were applied: the "Stimulating Classroom Environment Scale" and the "Creative Thinking Test" on a sample of 250 students.The results revealed:• A high overall level of both the stimulating classroom environment and creative thinking among the sample.• A strong, positive, and statistically significant correlation between the stimulating classroom environment and creative thinking.• Statistically significant differences in creative thinking levels in favor of females compared to males.• Statistically significant differences in creative thinking levels in favor of sixth-grade students compared to their counterparts in the fourth and fifth grades.The study concluded that the classroom environment plays a pivotal role in developing creative thinking. It recommended the necessity of improving spatial flexibility and providing resources, designing activities that specifically target the development of originality, training teachers on creative teaching strategies, and reviewing curricula to systematically support creativity.